A structured indicator pool to operationalize expert-based ecosystem service assessments for marine spatial planning. (1st April 2020) - von Thenen, Miriam; Frederiksen, Pia; Hansen, Henning Sten; Schiele, Kerstin S.
Abstract: There is growing evidence that the ecosystem service (ES) concept can provide valuable input to marine spatial planning (MSP), by highlighting which ecosystem goods and services can be produced from a planning area. ES link the underlying ecosystem processes and functions to the benefits humans can receive from ecosystems (the ecosystem cascade). In this study, we argue that the ecosystem cascade can be used to structure the stock-taking and future scenario analysis in MSP. However, indicators, which are needed for measuring ES, have often been applied in various ways to the different steps of the cascade. Here, we apply a consistent approach to sorting indicators into the cascade. The indicators are presented in an indicator pool that can be used to filter them based on the cascade steps, several quality criteria, and themes. The pool consists of 772 indicators, of which 735 were analyzed. In total, 252 analyzed indicators belong to the provisioning services, 314 indicators to the regulating services and 169 to the cultural services. The indicator pool offers a suitable starting point to select indicators for ES assessments within MSP. Using indicators at the different cascade steps allows the assessment of i) the ecosystem components generating the services and ii) the impacts on ES and their beneficiaries when changes occur in the provision of the services due to planning or management decisions. Highlights: An indicator pool for assessing the flow of marine ecosystem services (ES). The 735 indicators cover 51 relevant marine biotic and abiotic ES classes. They are structured into capacity, service, benefit and value indicators. The indicators are quality-checked and aggregated into indicator themes. The indicator pool provides a common starting point for ES assessments in MSP.